The Police and International Human Rights Law (Springer International Publishing, 2018)
This book provides an updated overview of current international human rights law relating to the police. Around the globe, the police have a special responsibility for the protection of human rights. Police work is governed by national rules and in addition, in today's world, by the evolving international human rights standards. As a result of the ever-developing case law of international courts and other bodies, the requirements of human rights law on policing have become more and more detailed and complex in recent years. Bringing together a variety of distinguished authors from academia, police forces and other government authorities, the human rights movement, and international organizations, the book discusses topical issues, including the use of deadly force, the prevention of torture, effective investigations, the protection of personal data, and positive obligations of the police.